PRODUCT DISTRIBUTION ROUTE OPTIMIZATION TO MINIMIZE TRANSPORTATION COSTS WITH THE SAVING MATRIX METHOD AT PT. XYZ - endah dwi yulianto (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2024)
XYZ is a company engaged in the packaged cooking oil industry. In the process of marketing, the products are delivered by truck directly to each distributor location in the area of Central Java and East Java. The company has problems in terms of planning is not optimal distribution of goods to the distributor. The obstacle is the use of capacity transportation is less than the maximum. Application of the saving matrix method in this study is expected to assist planning in maximizing the capacity of the conveyance and determining the optimal distribution channel so that the process of distributing the product can be run either every product shipped, both the number of products and the route of destination with low distribution costs. The results of the research conducted show that this method produces better efficiency, with an efficiency rate range of 13.4%, distribution costs Rp. 1,972,500,-, fuel costs 12.5% and some sub routes into 4 routes.